Dampak Gadget Bagi Anak Usia Dini Pada TK Islam Mutiara Amaliyah Dalu X B Tanjung Morawa - Dessy Ariani Hasibuan; Fia Novita; Isra Hayati; Zailani Zailani (Al-Ulum: Jurnal Pendidikan Islam, 2022)
The objectives of this study include (1) to determine the impact of gadgets on early childhood in the kindergarten; (2) Analyzing the ways in which parents control their children's gadget use; (3) Knowing how parents of students overcome gadget addiction in their children. The approach used in this research is descriptive qualitative method in the form of interviews with parents of students. Research in the form of interviews with several sources found that there are two effects of gadgets for early childhood in the kindergarten, namely the positive impact and negative impact. The way some parents control the use of gadgets for their children is also different. Moreover, overcoming gadget addiction for their children. Based on the results of the study, it can be said that the impact of gadgets for early childhood is quite large. Both positive impacts that increase knowledge, as well as negative impacts that make children indifferent to the environment.